Intergenerational social mobility and suicide risk by firearm and other means in US males. (December 2022) - Chapman, Benjamin P.; Peters, Kelly; Kannan, Viji; Hutchison, Morica; Lapham, Susan; Caine, Eric D.; Conner, Kenneth R.
Abstract: Firearms are the leading method of suicide in US men, and socioeconomic status (SES) is associated with suicide risk. In this 40-year mortality follow-up of a national cohort of US men, we examined if improved SES relative to one's family of origin, upward intergenerational social mobility (ISM), is associated with lowered risk for firearm suicide and suicide by other means in US men. Family of origin SES was assessed as part of Project Talent, a broad survey of US high school students in 1960. 42, 766 men in the cohort completed follow-up surveys at age 29, assessing attained SES via education, occupation, and income. ISM was measured by change between harmonized SES composites. Mortality follow-up was conducted through age 70. Adjusting for baseline SES and race/ethnicity, a 1 standard deviation increase in SES was associated with a 31% reduction in firearm suicide risk later in the life course (HR [95% CI] = 0·69 [0·54, 0·88], P = 0·003), and a smaller, non-significant reduction in suicide by other means (HR [95% CI] = 0·80 [0·60, 1·07], P = 0·136). Traits associated with both suicide and SES attainment (cognitive ability, calm, impulsivity) only modestly attenuated this association. Upward ISM was more strongly associated with reduced firearm suicide risk in males with parents of low SES. The association between upward ISM and reduced firearm suicide mortality risk prevailed over ensuing decades. Policies improving social mobility in US males, particularly those of lower SES, may function as de-facto firearm suicide prevention strategies.